The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1080/20008198.2019.1688130
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in grief narrative construction: a myth or reality?

Abstract: Background: Narratives play a central role in the recovery process following death, and linguistic properties of grief narratives can serve as indicators of adjustment to loss. The present study examined whether bereaved men and women differ in how they discuss their loss, and how linguistic markers relate to psychological functioning. Positive associations were hypothesized between first-person singular pronoun use and psychological distress. Gender differences were expected for different emotion and social p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Yet considering that the female might be at higher risk for PGD following violent loss (73), the high amount of male in our sample might have lowered the prevalence of probable PGD diagnosis. Furthermore, gender-specific processes or social norms might influence the way that individuals express grief symptoms (74,75). These aspects need further exploration.…”
Section: Further Findingsmentioning
confidence: 99%
“…Yet considering that the female might be at higher risk for PGD following violent loss (73), the high amount of male in our sample might have lowered the prevalence of probable PGD diagnosis. Furthermore, gender-specific processes or social norms might influence the way that individuals express grief symptoms (74,75). These aspects need further exploration.…”
Section: Further Findingsmentioning
confidence: 99%
“…On the one hand, the father is imbued with a social role of providing physical and emotional support for mothers, rendering his feelings, experiences and needs invisible [30]; on the other hand, the attachment and bond of a father is considered to be more rational and less passionate [31] since a mother creates her bond with the fetus from the first weeks of pregnancy and this is reaffirmed with fetal movements [32]. However, the risk of dysfunctional grief and the symptoms of psychological trauma is common in both sexes [33,34], although less studied in fathers [29].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a recent study examining grief narratives in a small sample of bereaved adults revealed a relationship between men's use of linguistic nonfluencies (e.g., "uh," "um," etc.) and their self-reported psychological distress, but this relationship did not emerge among women in the sample (Stelzer et al, 2019). One possible explanation for this pattern is that, because men are socialized to remain tough and stoic, men might have had less practice expressing their grief in emotionally vulnerable ways, which would facilitate their capacity to draw meaning from the experience of loss.…”
Section: Why Support Men's Emotional Flexibility?mentioning
confidence: 86%